2008
DOI: 10.1080/10668920701884505
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Barriers Concerning Effective Online Teaching and Policies: Florida Community College Faculty

Abstract: This study's purpose was to examine the perceptions of Florida's full-time community college faculty members who teach by distance learning concerning the ten policy areas set forth by Berge and Muilenburg (2000). Focus group sessions indicated that faculty members felt certain barriers related to their online experiences. Faculty time and compensation, which deals with how much time faculty members spend and how much they are compensated, seemed to be the greatest barrier while access seemed to cause faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 3 publications
2
51
1
3
Order By: Relevance
“…In fact, Bolliger and Wasilik (2009) found that some of the most significant institutional issues affecting faculty satisfaction were a higher workload and increased time commitment for online instructors. Many other studies have acknowledged issues of substantial time commitments and workload for online faculty (Bacow et al, 2012;Christianson et al, 2002;Conceição, 2006;DeGagne & Walters, 2010;Green et al, 2009;Haber & Mills, 2008;Mason et al, 2010). Most research has shown that time commitment and workload were barriers or demotivators to faculty, though some studies claimed that the extra time commitment did not affect faculty satisfaction or preference for teaching online (Christianson et al, 2002;Orr et al, 2009;Shea et al, 2005).…”
Section: Results Demonstrabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, Bolliger and Wasilik (2009) found that some of the most significant institutional issues affecting faculty satisfaction were a higher workload and increased time commitment for online instructors. Many other studies have acknowledged issues of substantial time commitments and workload for online faculty (Bacow et al, 2012;Christianson et al, 2002;Conceição, 2006;DeGagne & Walters, 2010;Green et al, 2009;Haber & Mills, 2008;Mason et al, 2010). Most research has shown that time commitment and workload were barriers or demotivators to faculty, though some studies claimed that the extra time commitment did not affect faculty satisfaction or preference for teaching online (Christianson et al, 2002;Orr et al, 2009;Shea et al, 2005).…”
Section: Results Demonstrabilitymentioning
confidence: 99%
“…Faculty were more negative about the legitimacy Faculty were more satisfied teaching online (2008) when they believed students were achieving Haber & Mills (2008) learning outcomes Jaschik & Lederman (2014) Johnson (2008) McQuiggan ( Extra time to teach online was a barrier for some faculty.…”
Section: Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…enseñar a los estudiantes a resolver problemas de procedimiento). En este caso, dar apoyo técnico suficiente al profesorado y a los estudiantes es sumamente importante (Haber y Mills, 2008).…”
Section: Barreras En La Implementación De La Educación a Distanciaunclassified